The Development of Interactive Learning Media Based on Visual Basic for 8th Grade Junior High School in Application (VBA) on Additive, Addictive and Psychotropic Substances - Wati, Erlina; Afiqah, Nurul; Sari, Anggi Kusuma; Rahmayumita, Restesa; Nasir, Muhammad (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This study aims to develop interactive learning media. The research method used is the ADDIE development research method. There are five stages of developing this interactive media, namely analysis, design, development, implementation, and evaluation. The assessment instrument consists of three experts and users. The data analysis technique used is the descriptive data analysis technique. The data that has been analyzed is then described qualitatively to find out the research category in each aspect, the design aspect with an average score of 0.819 with the high category, the pedagogic aspect 0.817 with the high category, the content aspect 0.817 with the high category, then for the last aspect the technique 0.07 moderate category. The developed simulation can be used, interactive, and can explain the concept well. Keywords: Addictive Substances, Learning Media, Interactive, Powerpoint VBA.